Commercialising disadvantage: the neoliberal discourses of commercial bail bond websites - Harrington, Leigh; et al. (Language and Law / Linguagem e Direito, 2022)
The commercial bail bond industry is one of the most profitable aspects of America’s highly marketized criminal justice system that is increasingly shaped by neoliberal structures and ideologies. Drawing on a specialised corpus of “Home” and “About Us” pages from bail bond websites, this paper is the first empirical linguistic examination of commercial bail bonds discourse grounded in its legal context. Using corpus-assisted critical discourse analysis, we examine how bail bond companies 1) discursively present and promote their services, 2) represent the legal system and its processes, and 3) construe arrest and detention to prospective service users. The findings show that bail bond companies position their services as an unobjectionably common (Brookes and Harvey 2017a) part of legal and financial self-management by normalising, legitimising, and idealising their use whilst seeking to minimise the power-imbalance between themselves and their often financially and socially disempowered ‘clients’. By grounding our linguistic analysis in a legal context, we demonstrate that these discourses simultaneously serve whilst oppress those they purport to help, offering an example of a local form of structural violence that subtly perpetuates neoliberal agendas and a two-tier justice system.